2018
DOI: 10.1128/genomea.01490-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Rice hoja blanca tenuivirus Isolated from a Susceptible Rice Cultivar in Colombia

Abstract: We describe here the complete genome of Rice hoja blanca tenuivirus. The sequenced isolate was obtained by insect vector transmission from a symptomatic rice sample grown in Colombia. Sequence data from the four RNA components were obtained by deep sequencing (Illumina), and infections were confirmed by enzyme-linked immunosorbent assay and Sanger sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…For instance, in a co-infected rice plant, PCR-positive for rice tungro spherical virus (RTSV, Waikavirus, Secoviridae ) and rice tungro bacilliform virus (RTBV, Tungrovirus, Caulimoviridae ), only RTBV-derived siRNAs could be readily identified by deep sequencing, while RTSV-specific reads were negligible and comparable to those in a control “virus-free” plant ( Zarreen et al, 2018 ). Since another waikavirus and viral species from other genera of Secoviridae are readily identified by small RNA sequencing (see Supplementary Table S1 and references therein) and because rice plants can generate siRNAs from many types of RNA and DNA viruses ( Yan et al, 2010 ; Jiang et al, 2012 ; Xu et al, 2012 ; Kreuze, 2014 ; Rajeswaran et al, 2014a ; Hong et al, 2015 ; Wu J. et al, 2015 ; Xu and Zhou, 2017 ; Yang et al, 2017 ; Jimenez et al, 2018 ; Lan et al, 2018 ; see Supplementary Table S1 and Supplementary List S1 ), the failure to identify RTSV-specific siRNAs can be explained by low titer of the virus. In this and other similar cases, deeper sequencing of small RNA-ome could have helped to uncover viral siRNAs.…”
Section: Toward More Exhaustive Reconstruction Of Complex Viromes By mentioning
confidence: 99%
“…For instance, in a co-infected rice plant, PCR-positive for rice tungro spherical virus (RTSV, Waikavirus, Secoviridae ) and rice tungro bacilliform virus (RTBV, Tungrovirus, Caulimoviridae ), only RTBV-derived siRNAs could be readily identified by deep sequencing, while RTSV-specific reads were negligible and comparable to those in a control “virus-free” plant ( Zarreen et al, 2018 ). Since another waikavirus and viral species from other genera of Secoviridae are readily identified by small RNA sequencing (see Supplementary Table S1 and references therein) and because rice plants can generate siRNAs from many types of RNA and DNA viruses ( Yan et al, 2010 ; Jiang et al, 2012 ; Xu et al, 2012 ; Kreuze, 2014 ; Rajeswaran et al, 2014a ; Hong et al, 2015 ; Wu J. et al, 2015 ; Xu and Zhou, 2017 ; Yang et al, 2017 ; Jimenez et al, 2018 ; Lan et al, 2018 ; see Supplementary Table S1 and Supplementary List S1 ), the failure to identify RTSV-specific siRNAs can be explained by low titer of the virus. In this and other similar cases, deeper sequencing of small RNA-ome could have helped to uncover viral siRNAs.…”
Section: Toward More Exhaustive Reconstruction Of Complex Viromes By mentioning
confidence: 99%
“…This work was supported by EMBRAPA (project 32. 16.04.037.00.00: Viral population analysis and management strategies for the common mosaic in wheat in Brazil), Fundação de Amparo à Pesquisa e Inovação do Estado de Santa Catarina (FAPESC -PAP) (Grant number: PAP2018), and UDESC. F.S.P.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Comparative analysis revealed that this protein shares 82% and 80% amino acid sequence identity with the RdRPs of FSaV and RHBV, respectively. RHBV was described in 1983, infecting rice in Colombia; and FSaV was described in 2021, infecting festuca in Germany [15][16][17]. The putative proteins encoded by RNA2 share 74% and 71% identity with the viral proteins pv2 of IWSV and pc2, encoded in the complementary sense of FSaV, respectively.…”
mentioning
confidence: 99%
“…Several studies (Table 2) involving the use of NGS for genome sequencing (complete or partial), detection, and characterization of RNA viruses infecting potato (S. tuberosum and S. phureja) (Gutiérrez-Sánchez et al, 2014;Villamil-Garzón et al, 2014;Muñoz et al, 2016;Vallejo C et al, 2016), peanut (Gutiérrez Sánchez et al, 2016), rice (Jimenez et al, 2018), cassava (Carvajal-Yepes et al, 2014), exotic fruits, such as Solanum quitoense (Gallo et al, 2018), Solanum betaceum , Physalis peruviana (Gutiérrez et al, 2015), Passiflora edulis (Jaramillo Mesa et al, 2018;Jaramillo Mesa et al, 2019), and horticultural products (Gutiérrez et al, 2017;Muñoz Baena et al, 2017) have been included. The above studies have been conducted using mainly total RNA isolated from symptomatic virus infected plants followed by depletion of rRNA and whole RNA sequencing.…”
Section: Ngs Applied To Plant Viral Genomicsmentioning
confidence: 99%
“…The above studies have been conducted using mainly total RNA isolated from symptomatic virus infected plants followed by depletion of rRNA and whole RNA sequencing. Plant viral genome reconstruction has been obtained by combining de novo transcriptome assembly for filtering contigs and sequences related to the virus and genome reference based on transcriptome assembly; however, few studies (Carvajal-Yepes et al, 2014;Jimenez et al, 2018) have been conducted using sRNA from virus-infected tissues.…”
Section: Ngs Applied To Plant Viral Genomicsmentioning
confidence: 99%